2010
DOI: 10.1115/1.4001982
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Future Aero-engine Designs With Intercooled and Intercooled Recuperated Cores

Abstract: Reduction in CO 2 emissions is strongly linked with the improvement of engine specific fuel consumption, as well as the reduction in engine nacelle drag and weight. Conventional turbofan designs, however, that reduce CO 2 emissions-such as increased overall pressure ratio designs-can increase the production of NO x emissions. In the present work, funded by the European Framework 6 collaborative project NEW Aero engine Core concepts (NEWAC), an aero-engine multidisciplinary design tool, Techno-economic, Environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…The cycle optimization results for the two powerplants are given in Table 2. Significant block fuel benefits are projected for the intercooled core engine, but they are smaller than those predicted in previous efforts [7]. This is mainly attributed to a minimum blade height requirement setting a practical lower limit on the intercooled core size for a given OPR.…”
Section: Fuel-optimal Designsmentioning
confidence: 68%
“…The cycle optimization results for the two powerplants are given in Table 2. Significant block fuel benefits are projected for the intercooled core engine, but they are smaller than those predicted in previous efforts [7]. This is mainly attributed to a minimum blade height requirement setting a practical lower limit on the intercooled core size for a given OPR.…”
Section: Fuel-optimal Designsmentioning
confidence: 68%
“…More details on these studies can be found in Kyprianidis et al (2011) and Larsson et al (2011). For the intercooled core assessment, a year 2020 Entry Into Service (EIS) turbofan engine with a conventional core was set up as the baseline.…”
Section: Summary Of Design Space Exploration Resultsmentioning
confidence: 99%
“…The prediction of engine performance, aircraft design and performance, direct operating costs and emissions for the concepts analysed in this study was made using the code described in [6]. Another code described in [7], was also used for carrying out the mechanical and aerodynamic design in order to derive engine component weights and dimensions. The two tools have been integrated together within an optimizer environment as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal efficiency benefits from intercooling have been well documented in the literature -see for example [2,3,7,9,[11][12][13]15]. Very little information is available however, with respect to design space exploration and optimisation for minimum block fuel at aircraft system level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation